Pasteurization Effects on the Microbial Ecology of Functional Tempeh Developed from Black Rice Bran and Dual Rhizopus Strains - Safrida Safrida; Slamet Budijanto; Lilis Nuraida; Bambang Pontjo Priosoeryanto; Nasrianti Syam (Universitas Labuhanbatu, 2025)
Background: Black rice bran has the potential to be a functional food raw material due to its high content of bioactive compounds; however, it is susceptible to microbial contamination. This study aims to evaluate the effect of pasteurization on the microbiological quality of fermented rice bran tempeh using Rhizopus oligosporus and Rhizopus oryzae. Methodology: The study employed a comparative experimental approach, where fermented for 72 hours with R. oligosporus and R. oryzae, grown in PDA medium, with the addition of spore suspensions at 15% each (10⁶ spores/mL). After fermentation, the bran was divided into two groups: one group was steamed for 10 minutes, while the other group was not steamed. Both groups were freeze-dried for 24 hours and then stored at -18 °C for analysis of changes in the profiles of total microbes, total fungi, total enterobacteria, and total spores. The raw material of rice bran was also analyzed microbiologically as a control. Microbiological data were analyzed using the Generalized Linear Model (GLM) and further evaluated by Duncan Multiple Range Test (DMRT) at a 5% significance level, as determined by SPSS 22.0 software. Findings: The results showed the pasteurization on bran tempeh products was effective in reducing the total number of microbes, moulds, Enterobacteriaceae, and spores compared to those without pasteurization. However, bran tempeh with R. oligosporus culture between pasteurized and unpasteurized did not show a significant decrease (p>0.05), except for the results of the analysis of the total number of moulds which showed a significant decrease (p<0.05), which was <1 log CFU/g (pasteurization) and 3.52 log CFU/g (without pasteurization). It can be concluded that the 10 minutes pasteurization process is effective in reducing the number of Enterobacteriaceae, which are indicators of polluting and pathogenic bacteria. Contribution: this treatment has potential to be applied on a home industry and Micro, Small and Medium Enterprises (MSME) scale to improve safety and extend the shelf life of fermented food products based on bran.